When legitimacy becomes the object of politics: the politicization of political support in European democracies - van Ham, Carolien; van Elsas, Erika (Frontiers in Political Science, 2024)
Democratic legitimacy is essential for democratic stability, as democracies rely on citizen support to survive. However, perceived legitimacy gaps can also be an important catalyst for change and potential democratic renewal, begging the question when challenges to legitimacy become problematic for democratic survival. Easton distinguished between citizen support for political authorities and the political system, and argued that if support for political authorities declined, such declining support could either be resolved by the current political authorities changing course, or by citizens electing new political authorities at the next elections. However, if dissatisfaction with political authorities would not be resolved, lacking support had the potential to eventually “spill-over” and undermine support for the political system as a whole. In most empirical research on legitimacy, the assumption is that such “spill-over” is visible only if declining levels of political trust and satisfaction with democracy start to undermine support for democracy as a political system. In this paper, we argue that “spill-over” can also manifest in a different way: through the politicization of political support. When politics is no longer (only) about substantive policy decisions, but rather (increasingly) about the system itself, agreement on the rules of the game, or even on democracy as “the only game in town”, is no longer self-evident. In this paper we further develop our theoretical argument about the connection between legitimacy and politicisation, and argue that European democracies appear to experience growing politicization of political support, in terms of the association of political support with citizens’ substantive issue positions and voting behaviour. The paper demonstrates empirical evidence of such politicization of political support in 17 European democracies with European Social Survey data from 2002–2022. The paper concludes by reflecting on the implications of the politicization of political support for democratic stability and renewal.